Access to medicines and vaccines : implementing flexibilities under intellectual property law - Correa, Carlos María; Hilty, Reto M., 1958- (Springer, 2022)
"This book is an outcome of a partnership between the Max Planck Institute (MPI) for Innovation and Competition and the South Centre, which jointly organized a Global Forum on Intellectual Property, Access to Medicine and Innovation in Munich on 9-10 December 2019"--Page v